Video feedback intervention: a case series in the context of childhood hearing impairment. Issue 6 (19th July 2013) - James, Deborah M.; Wadnerkar‐Kamble, Meghana B.; Lam‐Cassettari, Christa
Abstract: Background: Recent research shows that parental sensitivity can explain a significant and unique amount of growth in speech and language outcomes in children with cochlear implants. In this intervention study we explored the impact of an intervention designed to support parental sensitivity on children's communication development. Aims: This study tests the effect of a complex intervention in the context of childhood hearing impairment using a case study design of three families. Propositions for each case were made using parental report of the child's development in an attempt to identify change in outcome measurements that were not likely to be due to general development in the child or a halo effect from the intervention. Methods and Results: Multiple pre‐ and post‐intervention measures were taken. Outcome measures were mother–child contingencies to vocal utterances, emotional availability and an assessment of early communication in the child. Results for each case showed that improvements in some outcome measurements were found after the intervention and were maintained at follow‐up. Conclusions & Implications: Taking account of developmental change in intervention studies with children is challenging. Single‐subject intervention studies can be designed to allow research interventions to be tailored to meet families' specific needs. Video interaction guidance may support pre‐linguistic communicative development in children with hearing impairment.